Pemulihan Paska Longsor : Resiliensi dari Komunitas dan Konstruksi Setempat - Hidayati, Zakiah; Noviana, Mafazah (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Post-disaster recovery of landslides is a big challenge when the available resources are limited. Recovery includes the phases of rehabilitation and reconstruction. It was based on the guidelines of BNPB (National Disaster Management Authority) in Indonesia. This case-study research analyzed the resilience principle for post-disaster recovery. The locus was at Selili Hill, an urban village in Samarinda, East Kalimantan (Indonesia), with several landslides (land creeping) events over the last twenty years. The community and local construction discuss the resilience principle. This study found that the contribution of community resilience and local construction has a significant role to play in the housing recovery. Community involvement was very active during a disaster. They worked with the local government to provide food supplies and emergency shelter to those in need. As a result, the house rehabilitation was quite successful, focusing on social (income) and physical condition. We hope that the post-disaster rehabilitation concept and demonstration will be durable until the local government relocates the settlement.